Developing an Expertise-Specific P5 Module for Vocational Education: An ADDIE-Based Design - Anis Rahmawati; Agusti Tamrin; Ponco Adi Septiawan; Yusmarwati Yusof (Jurnal Pendidikan Vokasi, 2026)
Despite the implementation of the Merdeka Curriculum's Pancasila Student Profile Strengthening Project (P5) in Indonesian vocational schools, existing modules remain generic across expertise programs, limiting their effectiveness in integrating character development with vocational competencies. This study aimed to develop and validate an expertise-specific P5 module with an employment theme for the Building Modeling and Information Design (BMID) program using the ADDIE instructional design model. Development research was conducted through the five ADDIE stages involving P5 facilitators, subject matter experts, media experts, observers, teachers, and Grade XI BMID students. The developed module underwent expert validation and field implementation to evaluate its feasibility and instructional effectiveness. The results demonstrated high feasibility ratings from content experts (86.67%), media experts (90.91%), teachers (90.00%), and students (87.01%), indicating that the module is highly suitable for vocational learning. Unlike generic P5 modules, the developed module integrates BMID-specific technical competencies, authentic project-based learning activities, and employment-oriented contexts while simultaneously strengthening Pancasila character dimensions. This study contributes a systematic and replicable framework for developing expertise-specific P5 modules and provides practical guidance for vocational educators and curriculum developers in designing contextually relevant learning resources that enhance both vocational competence and character development under the Merdeka Curriculum.